Tocilizumab (monoclonal anti-IL-6R antibody) reverses anlotinib resistance in osteosarcoma - Xu, Jiuhui; Chen, Chenglong; Sun, Kunkun; Shi, Qianyu; Wang, Boyang; Huang, Yi; Ren, Tingting; Tang, Xiaodong (Frontiers in Oncology, 2023)
Tumor relapse and pulmonary metastasis are the major cause of poor prognosis of patients with osteosarcoma (OS). Recent antitumor agent research has seen the clinical application of several tyrosine kinase inhibitors (TKIs), such as anlotinib, with specific inhibition of malignant cell growth and metastasis in OS. However, as usually found for antitumor drugs, a variety of resistance phenomena have been observed in the treatment of OS with TKIs. In this study, we established four OS anlotinib-resistant cell subtypes wherein we evaluated activation of the cytokine-cytokine receptor interaction pathways, especially the up-regulated expression of interleukin-6 (IL-6) and its downstream STAT3 pathway. We further explored the effects of tocilizumab, a clinically used monoclonal anti- IL-6 receptor (IL-6R) antibody, either alone or in combined with anlotinib, on the inhibition of anlotinib-resistant OS cells and xenograft nude mouse model. Notably, tocilizumab impaired the tumor progression of anlotinib-resistant OS cells, and combined treatment with anlotinib augmented these effects by inhibiting STAT3 expressions. Tocilizumab could reverse anlotinib resistance in OS and this rationalized further studies and clinical use of tocilizumab in the treatment of anlotinib-refractory OS.